High Temperature Oxidation Behavior of ODS Ferritic Stainless Steel Fe-16Cr-4Al-1Ni-0.4Y2O3 - Wafda, Hakimul; Prajitno, Djoko Hadi; Basuki, Eddy Agus; Syafiq, Ahmad; Widiawati, Nina; Andi Mustari, Asril Pramutadi (Indonesian Journal of Chemistry, 2024)
This study investigates the isothermic oxidation behavior of the new ODS alloy Fe-16Cr-4Al-1Ni-0.4Y2O3 (% by weight) at 700, 800 and 900 °C, with exposure times of 5, 20, 50, and 100 h at each temperature. The purpose is to obtain new data on its high-temperature parabolic oxidation constant for assessing oxidation resistance. The methods used include isothermal oxidation testing, XRD, SEM-EDS characterization, and analysis of oxidation kinetics by monitoring changes in oxide thickness using microscopy and SEM-EDS. The oxide products formed on the sample surface are Fe2O3, Fe3O4, AlFe2O4, and (Fe,Cr)2O3. Al and Cr oxides are located under the dominant Fe oxide layer on the surface of the sample. The oxidation test results showed that the most protective sample was obtained at a temperature of 700 °C for 100 h with an oxide thickness of 263.99 μm. The kinetics analysis correlates strongly with the parabolic equation (R2 ≈ 1). The oxidation rate constants at temperatures of 700, 800, and 900 °C were 681.76, 2957.5, and 12300 μm2 h−1, respectively. The activation energy required by the oxidation reaction in this alloy is 136.5 kJ mol−1. This research enhances understanding and potential applications of the Fe-16Cr-4Al-1Ni-0.4Y2O3 alloy in high-temperature environments.